2020
DOI: 10.1007/s10657-020-09644-8
|View full text |Cite
|
Sign up to set email alerts
|

Legal forms, organizational architecture, and firm failure: a large survival analysis of Russian corporations

Abstract: In this paper, we trace the survival status of more than 110,000 Russian firms from 2007-2015 and examine the relationship between legal forms of incorporation and firm survivability across industries and different periods of economic crisis and growth. Applying the Cox proportional hazards model, we find an optimal legal form that maximizes the probability of firm survival: closed joint-stock companies and those adopting limited liability survive longer than open joint-stock companies, partnerships, or cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In Europe, in the early 1990s, multinational firms from developed economies launched numerous acquisitions in connection with massive privatizations of state-owned companies during the economic transformation of Central and Eastern European (CEE) countries (Estrin et al, 2009;Meyer et al, 2009;Iwasaki and Mizobata, 2018). Recently, the global financial crisis (GFC) has hit hard CEE companies (Hanousek et al, 2015), leading many of them into financial distress and forcing some to exit the market (Baumöhl et al, 2019;Iwasaki and Kim, 2020;Iwasaki et al, 2021). Under these circumstances, takeovers by stronger counterparts represent a viable solution for restructuring the assets of distressed firms, as a takeover may serve as an emergency-resolution mechanism instead of bankruptcy (Stiglitz, 1972).…”
Section: Introduction Motivation and Related Literaturementioning
confidence: 99%
“…In Europe, in the early 1990s, multinational firms from developed economies launched numerous acquisitions in connection with massive privatizations of state-owned companies during the economic transformation of Central and Eastern European (CEE) countries (Estrin et al, 2009;Meyer et al, 2009;Iwasaki and Mizobata, 2018). Recently, the global financial crisis (GFC) has hit hard CEE companies (Hanousek et al, 2015), leading many of them into financial distress and forcing some to exit the market (Baumöhl et al, 2019;Iwasaki and Kim, 2020;Iwasaki et al, 2021). Under these circumstances, takeovers by stronger counterparts represent a viable solution for restructuring the assets of distressed firms, as a takeover may serve as an emergency-resolution mechanism instead of bankruptcy (Stiglitz, 1972).…”
Section: Introduction Motivation and Related Literaturementioning
confidence: 99%
“…There is empirical evidence showing that the ownership structure of firms matters in survival chances. Some authors have found that foreign-owned plants have a higher probability of exit than their domestic-owned counterparts in Ireland and Spanish manufacturing firms [24] [25] [26]. So, we proposed the following hypothesis:…”
Section: Ownershipmentioning
confidence: 94%
“…However, many firms entering the market at that time soon found it difficult to survive (McDermott, 2004). Moreover, an uneasy transformation process, along with the ensuing GFC, negatively impacted firms' performance and consequent survivability (Estrin et al, 2009;Hanousek et al, 2015;Baumöhl et al, 2019;Iwasaki and Kim, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we account for key firm-specific characteristics such as firm size and age, ownership structure, and financial performance. These factors affect the general ability of a firm to survive (Alfaro and Chen, 2012;Kočenda and Hanousek, 2012;Baumöhl et al, 2020;Iwasaki and Kim, 2020). At the same time, these factors, especially the size and age of the firm associated with the ability to attract financial resources, also affect small business failures; thus, they are repeatedly examined as control variables in prior studies.…”
Section: Introductionmentioning
confidence: 99%